The Information Content in Bonus Issue Announcements : Evidence from the Indian Corporate Sector - Basra, Heena; Singla, Ravi (Indian Journal of Finance, 2020)
The bonus issue has remained the center of attraction among researchers within the finance literature due to its puzzling nature. This study tried to revalidate two hypotheses namely, information signalling hypothesis and liquidity hypothesis in the Indian stock market in context of bonus issue announcements. Price reaction and trading volume on and around the announcement as well as ex-date were investigated during the study period (2004 – 2016). The study also measured the market depth through augmented liquidity tests around these two dates. The findings of the study observed significant positive abnormal reaction on the day of announcement as well as ex-bonus date. The presence of significant positive abnormal reaction in the pre-announcement period indicated the existence of insider trading and/or information leakages. The significant negative price reaction observed during the post ex-bonus day indicated the presence of bonus stripping practices in the study period. The study observed abnormally high trading volume around the announcement date and the ex-bonus date. The augmented liquidity tests, that is, stock’s trading volume, stock’s relative trading volume, and liquidity ratio revealed that stocks traded on NSE experienced enhanced liquidity in the post bonus issue period. The empirical findings of the research were in line with the information signalling hypothesis and liquidity hypothesis.